GmAKT1 is involved in K+ uptake and Na+/K+ homeostasis in Arabidopsis and soybean plants - Wang, Xuesong (Plant science : an international journal of experimental plant biology, 2021)
Copyright © 2020 Elsevier B.V. All rights reserved.